Jean-Luc Marion: ¿fenomenólogo? - Katz, Azul (2019)
“Jean-Luc Marion: Phenomenologist?”. How are we to understand the contradiction of a philosophy that claims to be a legitimate heir of the phenomenological tradition but, at the same time, intends to break free from its limits to allow an unconditioned manifestation? Should we comprehend Jean-Luc Marion’s work as a true renovation of phenomenology –as he and his followers do–, or should we instead consider it as a pure theology independent from the phenomenological movement? Why would the theological way be the only possible way out of the crisis of contemporary metaphysics denounced by Marion and, even more, a necessary way? To answer these and other questions, this paper develops some of the paradoxes that arise from the Marionian theological turn, distinguishing two possible ways of understanding its Kehre: either as a deviation that allows extending phenomenology to new fields, or as a return to and abandonment of the phenomenological project. Finally, we wonder if Marion’s proposal of a gradual ontology does not encourage a third possible way, which would lead us to think of his thought not as phenomenology anymore, but as a gradualist-theological fansiology.